The Effectiveness of Team-Based Care Approach in Managing Heart Attack Patients in Primary Care - Romauli Anna Teresia Marbun (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Primary healthcare facilities play a crucial role in delivering rapid and effective healthcare services, especially in managing medical emergencies. These emergency situations require a swift response and well-coordinated teamwork among various healthcare professionals. Interprofessional competencies can be enhanced through scenario-based simulations, allowing healthcare providers to train in a safe yet realistic environment. This article discusses strategies for implementing simulations to improve communication skills, team coordination, and healthcare professionals’ decision-making abilities. Simulations not only enhance healthcare workers' preparedness in emergency situations but also help reduce medical errors and improve patient safety. Through a systematic approach and continuous training, primary healthcare facilities can ensure that their healthcare providers possess optimal competencies in emergency management. Furthermore, the integration of technology in simulations, such as augmented reality and virtual reality, further strengthens the effectiveness of training. Therefore, incorporating simulations in interprofessional competency enhancement should be a key component of routine training policies for medical personnel in primary healthcare facilities.